2008
DOI: 10.1292/jvms.70.1273
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of VEGF and flt-1 in the Normal Dog Tissues

Abstract: ABSTRACT. Angiogenesis is essential for tumor progression and is regulated by several angiogenic factors such as vascular endothelial growth factor (VEGF). We investigated the expression and distribution of VEGF and its receptor flt-1 in twelve normal canine tissues in six beagle dogs using immunohistochemistry, RT-PCR and real-time RT-PCR. Immunochemical staining showed that both VEGF and flt-1 were expressed in many tissues and their mRNAs were detected in all organs examined by RT-PCR. Levels of VEGF164 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 12 publications
1
15
0
Order By: Relevance
“…The presence of VEGF receptors was also observed in healthy lung, skin and bladder tissue in dogs (Uchida et al, 2008).…”
mentioning
confidence: 74%
“…The presence of VEGF receptors was also observed in healthy lung, skin and bladder tissue in dogs (Uchida et al, 2008).…”
mentioning
confidence: 74%
“…VEGF-A, a strong angiogenic factor, is expressed at low levels in normal mammalian tissues; increased levels of VEGF-A were observed during ischemia or hypoxia, and in lesions characterized by angiogenesis. In a recent study [31], VEGF-A 120 , VEGF-A 164 , and VEGF-A 188 were detected in normal canine tissues, and VEGF-A 164 , which corresponds to human VEGF-A 165 , is the dominant molecular species. Canine VEGF-A 164 contains all the necessary information for the normal growth, remodeling, and patterning of blood vessels [32].…”
Section: Discussionmentioning
confidence: 99%
“…No studies have been published on the role of VEGF‐A in inflamed canine skin. One study reported the presence of VEGF isoforms and the receptor VEGFR‐1 in all tissues tested (liver, lungs, kidneys, heart, adrenal glands, thyroid, intestine, bladder, spleen and skin) in six healthy beagle dogs, with the highest concentrations in the lungs and heart . VEGF and its receptor were moderately to strongly evident in epidermis, sebaceous glands, apocrine glands, erector pili muscles and hair follicles .…”
Section: Discussionmentioning
confidence: 99%